2021
DOI: 10.3390/genes12050615
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Alternatively Spliced Transcript Isoforms of IRX4 in Prostate Cancer

Abstract: Alternative splicing (AS) is tightly regulated to maintain genomic stability in humans. However, tumor growth, metastasis and therapy resistance benefit from aberrant RNA splicing. Iroquois-class homeodomain protein 4 (IRX4) is a TALE homeobox transcription factor which has been implicated in prostate cancer (PCa) as a tumor suppressor through genome-wide association studies (GWAS) and functional follow-up studies. In the current study, we characterized 12 IRX4 transcripts in PCa cell lines, including seven no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…IRX4_PEP1 is 78 amino acids in length with an AUG canonical start codon and have a high CPPred-sORF coding potential of 91%. Our previous studies related to the IRX4 locus have identified a potential transcript variant that can encode IRX4_PEP1 and have validated its expression at the protein level in PCa cell lines (18).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…IRX4_PEP1 is 78 amino acids in length with an AUG canonical start codon and have a high CPPred-sORF coding potential of 91%. Our previous studies related to the IRX4 locus have identified a potential transcript variant that can encode IRX4_PEP1 and have validated its expression at the protein level in PCa cell lines (18).…”
Section: Resultsmentioning
confidence: 99%
“…Its expression is specific to PCa and increases with advanced PCa, suggesting its significance in this cancer type. In our previous study, a transcript variant of IRX4 that encode this miPEP was detected in both PCa cell lines and clinical samples (18). As a result, IRX4_PEP1 was chosen for further functional characterization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative splicing (AS) is a conserved biological process that allows the generation of several different mRNA isoforms from one gene locus [ 1 , 2 , 3 ]. This process occurs in close relation to transcription in eukaryotes [ 4 ].…”
Section: Introductionmentioning
confidence: 99%